Do surgeon interviewers have human factor-related issues during the long day UK National Trauma and Orthopaedic specialty recruitment process?. Issue 5 (October 2018) - Scrimgeour, D.S.G.; Higgins, J.; Bucknall, V.; Arnett, R.; Featherstone, C.R.; Cleland, J.; Lee, A.J.; Brennan, P.A.
Abstract: Purpose: The role that human factors (HF) play in contributing to medical error is increasingly being recognised by healthcare professionals. Surprisingly, much less is known about the possible effects of HF including boredom, fatigue and organisational influences, on performance outside of the clinical environment such as examining or assessing candidates in other high stakes situations. Methods: The authors used a validated 38 response questionnaire based around the HF analysis and classification system (HFACS) to assess factors including stress and pressure, care and support and working within the rules for surgeon interviewers at the UK national trainee selection process in Trauma and Orthopaedic surgery. Results: 121 completed questionnaires were analysed (86% response rate). No statistically significant differences were found between interviewer experience, grade or role at the interview and the mean scores obtained for all four factor items. Overall interviewers had a positive experience during national selection with mean factor scores ranging from 3.80 to 3.98 (out of a maximum satisfaction score of 5). Conclusions: Careful planning by organisations and recognising the importance of the human element are essential to ensure assessors are looked after properly during high stakes assessment processes. Our data suggests that a positive experience for examiners is likely to benefit candidate performance and contribute to a fair and reliable recruitment process. The relationship between examiner experience and candidate performance merits further investigation.